PENGARUH KEPEMIMPINAN PARTISIPATIF TERHADAP KEPUASAN KERJA GURU DI MADRASAH - Akhyar, Yundri (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2025)
The topic of job satisfaction among educators is frequently affected by the leadership style employed; however, the correlation between participative leadership and job satisfaction within Madrasah Aliyah has yet to be thoroughly investigated. This study seeks to examine the influence of participative leadership on the job satisfaction of educators within Madrasah Aliyah. A quantitative methodology utilizing a survey instrument was implemented, engaging a total of 326 educators as participants. Data were gathered via questionnaires and subsequently analyzed utilizing regression analysis to ascertain the relationship between participative leadership and job satisfaction. The findings suggest that participative leadership exerts a positive and statistically significant influence on teachers' job satisfaction. Educators who participate in decision-making processes and collaborative efforts experience a heightened sense of value and motivation. Subsequent analysis indicates that participative leadership significantly contributes to the variation in teachers' job satisfaction, highlighting the critical significance of fostering a supportive work environment. The findings of this study suggest that the implementation of participative leadership may significantly enhance the well-being of educators and subsequently improve the overall quality of education. These findings offer significant insights for policymakers and educational administrators to adopt more inclusive leadership strategies.